1983 ネン アイスランド ニ オケル オーロラ ゲンショウ ノ キョウヤクテン カンソク ホウコク - 佐藤, 夏雄; サトウ, ナツオ; 福西, 浩; フクニシ, ヒロシ; 国分, 征; コクブン, ススム; Saemundsson, Th.; Sato, Natsuo; Fukunishi, Hiroshi; Kokubun, Susumu (1984)
P(論文) 南極の昭和基地, みずほ基地, マラジョージナヤ基地の地磁気共役点であるアイスランドのHusafell, Isafjordur, Husavikの3点において, オーロラ現象の共役性を解明するための観測計画が, 昭和58年度より開始された。本年度は, IsafjordurとHusavikにおいて, ノイズ調査, センサー設置場所の選定などの予備調査を行った。また, Husafellでは, 本格的な観測システムの建設と連続観測を実施した。 This campaign has been organized by the National Institute of Polar Research as a cooperative project with the Science Institute, University of Iceland. This campaign aims at a further understanding of physical processes in auroras by a coordinated observation of magnetic field variations, magnetic ULF waves, ELF-VLF emissions, cosmic noise absorption, and spatial and temporal variations of auroras in the magnetically conjugate polar region. The campaign takes advantage of geographical condition that the conjugate points of Syowa, Mizuho and Molodezhnaya Stations in Antarctica are located in the vicinity of Husafell, Isafjordur and Husavik in Iceland. With the data recorded at the three conjugate station pairs Syowa-Husafell, Mizuho-Isafjordur, and Molodezhnaya-Husavik, we investigate the temporal and spatial conjugacy of both auroras and wave phenomena associated with auroral particle precipitation. Then we study the auroral particle acceleration process in the ionosphere-magnetosphere energy coupling system and also the generation and propagation mechanisms of ULF, ELF and VLF plasma waves. Three Japanese scientists have been in Iceland from August 12 to October 2. In the first half of the period of their stay they visited Isafjordur (66.1°N, 23.1°W) and Husavik (66.0°N, 17.4°W) to find locations suitable for observations of geomagnetic field variations, cosmic noise absorption and ULF, ELF and VLF natural waves. During their stay at Husafell, various kinds of sensors (fluxgate magnetometer, search coil magnetometer, ELF-VLF wave receiver, riometer and all-sky camera) and recording facilities were set up. These facilities are operated by the Icelandic research fellow until next summer. departmental bulletin paper